PENGENALAN BUDAYA HIDUP SEHAT DI TAMAN KANAK-KANAK MUSARA ALUN KABUPATEN TAKENGON - suminah, Suminah; Fitriyani, Fitriyani (Ta'dib: Jurnal Pemikiran Pendidikan, 2022)
Early childhood education is early education, often referred to as the golden age, therefore this period determines further development. One of the important aspects in determining a child's life in the future is to get used to living healthy in the environment around the child, while the environment around the child is the family, school and community environment, these parties are directly involved in fulfilling the early habit of healthy living. Since the COVID-19 pandemic and post-pandemic, it is necessary for all to maintain cleanliness and healthy living habits. The purpose of this research is how the teacher treats children to teach a healthy lifestyle, what kind of evaluation is done by the teacher to see the success of children in refracting a healthy lifestyle. The result of this research is the teacher's treatment of children to teach a healthy culture by using Storytelling, Habituation, Demonstration and Field Trip methods. The conclusion of the introduction of a healthy living culture in the Musara Alun Kindergarten, Takengon Regency is the habit of washing hands properly, Disposing of garbage in its place both at school and outside school, Brushing teeth in the morning and evening, Defecation and urination in the bathroom. , Nail cutting is sunnah once a week on Fridays, and Inspections from the local health center once a month.